PERCEPATAN PENGELOLAAN LIMBAH KOTORAN SAPI MENJADI KOMPOS TERSTANDAR - Mutmainnah, Laily; Ibanah, Indah; Yanuarti, Rizky; Luthfiyah, Lenny; Fitriani, Vivi; Harsanti, Restiani Sih (Universitas Halu Oleo, 2024)
Farmer groups in Trebengun Village are starting to have concerns about the reduction of subsidized fertilizers from the government which has an impact on crop production. On the other hand, most of the people of Trebungan have cattle that produce solid manure waste. Cow manure waste has not been used so far and has become an environmental pollutant in Trebungan Village. Cow manure waste is one of the materials that contains quite high nitrogen content. This condition can be a solution to meet the fertilizer needs of farmer groups. The purpose of the service activity is to process cow dung waste into solid organic fertilizer. Service activities consist of: a) Socialization, b) Assistance in fertilizer manufacturing practices, and c) Product feasibility evaluation. The manufacture of organic fertilizer made from cow dung is enriched with Local Microorganisms (MOL) to improve the quality and quality of fertilizer. The service activity runs for 3 months. The obstacle experienced during the manufacture of organic fertilizer is the inaccurate dosage of microorganism and water solutions applied to cow manure. However, the Farmer Group and the University of Jember Service Team can make organic fertilizers that are in accordance with national quality standards.